Perancangan Sistem Informasi Akuntansi Pendapatan Pada Arkan Graha Berbasis Web Menggunakan Php Dan Mysql - Kiki Hakiki Haryadi; Hery Dwi Yulianto (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2017)
Arkan Graha are addressed in jl. Cisaranten kulon III No.14A Arcamanik Bandung 40293 (022 87882775). Arkan Graha requires a good income information systems to handle various problems in the company, which include the income or expenditure reporting services that still use ms.excel and performed by one person, doing so in the company's earnings report to be less effective. To these problems, the writer took the title " Design Of Revenue Accounting Information System Web based At Arkan Graha Using PHP and MYSQLâ€. The research design used is primary or secondary research design, the type of data is qualitative data and quantitative data, the type of research used is academic research, data collection techniques that I use are field studies consisting of interviews and observation and literature, research methods using descriptive research methods and survey methods. System development methods use methodologies oriented to processes, outputs, and data, the development structure used is Waterfall